EFL PRE-SERVICE TEACHERS’ ANXIETY DURING TEACHING PRACTICE - Zaki, Leil Badrah; Salsabila, Annisa (Premise: Journal of English Education and Applied Linguistics, 2024)
The struggles that currently being the research interest in education is Pre-Service Teacher Anxiety. The anxiety can be seen not only “before” and “after”, but also "during" the experiences of the learning and teaching process with the learners. Can (2018) mentioned that among the pre-service teachers during the teaching practicum, they reported about their feeling of anxiousness during the process of teaching internship. Therefore, this research aims to identify the anxiety score and anxiety level of the Pre-Service Teacher during the teaching internship. The participant was the Pre-Service Teacher from universities in Indonesia. The research will use mixed methods as the methodology. Data will also be gathered from questionnaires and in-depth interview. The questionnaire is adapted from Student-Teacher Anxiety Scale (STAS) by Hart in (1987). From the result the researcher can define score and level of the Pre-Service Teacher anxiety during the teaching internship. Therefore, the process to be a Pre-Service Teacher in English Language Education needs to be equipped with sufficient training to lessen the anxiety, such as workshop and training courses.